Tensile Behavior of Directed Energy Deposited Bi-Metallic Ti-Ni-Based Alloy at Interfacial Area: Tensile Behavior of Directed Energy Deposited Bi-Metallic Ti-Ni-Based Alloy at Interfacial Area - Chen, Yitao; Ortiz Rios, Cesar; Liou, Frank (JOM (1989), 2025)
A Ti-Ni-based bi-metallic shape memory alloy was fabricated using directed energy deposition, and the tensile testing behavior at two sections after post-heat treatments were focused. The Ti-rich Ti-Ni-Cu ternary shape memory alloy was first fabricated on a TiNi shape memory alloy with near-equiatomic composition to achieve multi-functional shape memory behaviors using powder-based additive manufacturing. The bi-metallic part then underwent 400°C and 600°C heat treatment at the interfacial area, and the interfacial area was subject to tensile loading and unloading. The digital image correlation technique was applied to extract the tensile stress–strain behavior and map out the local strain evolution of different shape memory alloy sections of the bi-metallic structure. Significant differences in the local stress–strain behaviors of martensitic and austenitic TiNi phases were observed and discussed among various heat-treatment effects. The tensile study in this work indicates the strong capability of the directed energy deposition process to develop multi-sectional shape memory alloys with unique combined memory effects, and those unique mechanical behaviors can be clearly recorded and evaluated by digital image correlation.